Analisis Strategi Bersaing pada UKM Jus Buah (Studi pada Usaha Rayna Juice) - Sinaga, Marnidauli; Nasution , Muhammad Arifin (Regress: Journal of Economics & Management, 2022)
Increasingly competitive business competition requires small businesses to have a competitive advantage. The competitive advantage of SMEs can be achieved by developing products so that they are unique. Like the business of Rayna Juice as one of the SMEs that have competitors located on Tuasan street 65 Sidorejo Hilir subdistrict Medan Tembung district North Sumatera, which is still standing today. The purpose of this research is to implement the strategy used by Rayna Juice bussines Tuasan street 65 Sidorejo Hilir subdistrict, Medan Tembung district, North Sumatra. This researc uses a qualitative approach with descriptive analysis. Primary data collection techniques through observation, interviews. Meanwhile, secondary data were obtained from literature study and documentation. To analyze the data, the SWOT analysis method (Strenghts, Weaknesses, Opportunity, Threats) was used, namely by identifying internal and external factors, using the IFAS & EFAS table and the SWOT matrix. Based on the internal and external analysis and diagram of the SWOT matrix (Strenghth, Weakness, Opportunity, Threats) conducted by researchers, rayna’s juice was in favor of the aggressive (quadrant 1).Whereas rayna juice has a force of 2,36 greater than 0,43 weaknessses and the opportunity of 2,65are greater than the threat of 0,45.